Revisiting the Role of B-RAF Kinase as a Therapeutic Target in Melanoma - Kozyra, Paweł; Pitucha, Monika (Current Medicinal Chemistry, 2024)
Malignant melanoma is the rarest but most aggressive and deadly skin cancer. Melanoma is the result of a malignant transformation of melanocytes, which leads to their uncontrolled proliferation. Mutations in the mitogen-activated protein kinase (MAPK) pathway, which are crucial for the control of cellular processes, such as apoptosis, division, growth, differentiation, and migration, are one of its most common causes. BRAF kinase, as one of the known targets of this pathway, has been known for many years as a prominent molecular target in melanoma therapy, and the following mini-review outlines the state-of-the-art knowledge regarding its structure, mutations and mechanisms.
Keywords: structure